Design of medium entropy oxide for photo-Fenton catalytic degradation of tetracycline - Sachan D.; Singh N.; Kumar U.; Kuntail J.; Sinha I.; Singh R. (My University, 2025)
A dual-phase equiatomic multi-cation medium entropy oxide (FeCoNiMg)Ox (EMMEO) was investigated as a photo-Fenton catalyst due to its visible-light bandgap, compositional flexibility, and photo-thermal stability. The EMMEO was synthesized via an auto-combustion method and subsequently calcined at 800 °C for 2 h, resulting in a uniform distribution of Fe, Co, Ni, Mg, and O throughout the catalyst. It exhibited superparamagnetic behaviour, with a saturation magnetization of 53.8 emu/g and a low coercivity of 539.8 Oe. X-ray photoelectron spectroscopy (XPS) analyses of fresh and cycled (post-tetracycline degradation) samples confirmed the stability and reactivity of the EMMEO material. Scavenger experiments revealed that positive holes (h⁺) and hydroxyl radicals (•OH) were the primary active species, especially the latter, driving the photo-Fenton mechanism. UV–visible absorbance spectroscopy demonstrated 97.7 % degradation efficiency of tetracycline in 70 min. The study highlights the potential of medium entropy oxides in cost-effective photocatalytic applications. © 2025